RANCANG BANGUN SISTEM FEEDING MATERIAL KERJA OTOMAT PADA MESIN GERINDA POTONG ELEKTRO-PNEUMATIK - Panjaitan, David; Rantung, Jotje; Lumintang, Romels (Jurnal Poros Teknik Mesin UNSRAT, 2024)
The electro-pneumatic cutting grinding machine at the Mechanical Engineering Laboratory of UNSRAT Manado is used to insert the workpiece to be cut off at this present time, it still used manually or still requires human hands to work out, this makes the cutting process require a longer time, moreover, reducing the efficiency of time. Based on this case, this research conducts sustainable production technology and designs to makes an automatic work material feeding system on an electro-pneumatic cutting grinding machine. This study aims to design, as well as create a feeding system for automatic work control materials on an electro-pneumatic cutting grinding machine. The method used in this study is the design method by designing and manufacturing directly, based on the condition of the electro-pneumatic cutting grinding machine. The manufacturing process starts from identifying working drawings and components to be used using existing tools and machines, placing online orders, and using them from the market or other components. Furthermore, a feeding system of automatic work control materials can be made on an electro-pneumatic cutting grinding machine Keywords: Design, Feeding System, Cutting Grinding Machine1.